2021
DOI: 10.1186/s12885-021-08764-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for esophageal squamous cell carcinoma and its histological precursor lesions in China: a multicenter cross-sectional study

Abstract: Background Despite research efforts, the causative factors that contribute to esophageal squamous cell carcinoma (ESCC) in high-risk areas have not yet been understood. In this study, we, therefore, aimed to describe the risk factors associated with ESCC and its precursor lesions. Methods We performed an endoscopic examination of 44,857 individuals aged 40–69 years from five high incidence regions of China in 2017–2018. Participants were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…20 A high intake of meat, hot foods and beverages, and salty foods may increase the risk of EC, whereas an increased consumption of plant foods may decrease the risk of EC. 21,22 A high intake of vegetables and fruits may be of particular benefit in this context, 23 because both are abundant in folate, vitamin C, and polyphenols which may exert favorable effects on EC risk. 24,25 The composition of diet may also influence the body's acid-base balance 26 and a regular consumption of acidogenic dietary components may increase dietary acid load (DAL), which has been closely linked to chronic low-grade inflammation and subsequent cell transformation.…”
Section: Introductionmentioning
confidence: 99%
“…20 A high intake of meat, hot foods and beverages, and salty foods may increase the risk of EC, whereas an increased consumption of plant foods may decrease the risk of EC. 21,22 A high intake of vegetables and fruits may be of particular benefit in this context, 23 because both are abundant in folate, vitamin C, and polyphenols which may exert favorable effects on EC risk. 24,25 The composition of diet may also influence the body's acid-base balance 26 and a regular consumption of acidogenic dietary components may increase dietary acid load (DAL), which has been closely linked to chronic low-grade inflammation and subsequent cell transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies 30 used maternal blood serum and diet as markers of prenatal exposure and children’s serum as indicators of post-natal exposure. The data source for ALRI/URI includes the use of questionnaires 9 - 12 , 14 , 15 , 25 , 26 , 29 - 32 or medical records. 26 , 33 Due to cultural beliefs and community perception related to blood sampling, the current study sampled urine.…”
Section: Discussionmentioning
confidence: 99%
“…The district is made up of 17 small and 3 large farming communities. 11 , 12 The communities are socio-culturally and economically homogenous. The population of the North Offinso district is 83 440 of which about 32 210 live in Akumadan, Nkenkenson, and Afrancho.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the development of artificial intelligence (AI) has allowed NBI examinations to be further optimized, and AI model relying on convolutional neural network (CNN) can precisely identify NBI endoscopic images of cancer patients and improve the diagnostic efficiency of NBI [ 9 ]. The diagnostic value of the current AI model in gastrointestinal malignancies, such as colorectal cancer and gastric cancer, has been confirmed by literature at home and abroad [ 10 ], and Tan et al reported that the CNN-based AI model had a sensitivity of 90.12% and a specificity of 91.53% for the interpretation of NBI endoscopy in patients with laryngeal cancer [ 11 ], with exact application value.…”
Section: Introductionmentioning
confidence: 99%